HUBUNGAN ANTARA KEBIASAAN JARAK MEMBACA DAN KELELAHAN MATA TERHADAP KEJADIAN PRESBIOPIA - Fatimah, Mustika (JURNAL KESEHATAN TERAPAN, 2021)
Background: Presbyopia is an eye defect due to reduced accommodation power of the eye in old age. Reading with the distance between the eyes and the book too close will indeed cause dizziness and difficulty understanding because you only see the reading word for word. Eye fatigue can arise from reading, writing, driving for long periods of time.Methods:This analytical survey research with a cross sectional approach was conducted in 2020 with a minimum sample size of 52 people using simple random sampling technique. Data obtained through interviews using questionnaires and examination of refraction and analyzed by univariate and bivariate using SPSS ver 25.0.Results:There was a significant relationship between reading distance habits and eye fatigue with the incidence of presbyopia (p value = 0.008). Conclusion:There is a significant relationship between reading distance habits and eye fatigue with the incidence of presbyopia, this can be used as input for developing health services. Keywords: Eye Fatigue, Presbyopia Reading Distance